How can a leading company in the beauty industry collaborate with retailers to improve its omnichannel performance - Nogueira, Ricardo Filipe Ferreira (2022)
This study analyzes the omnichannel performance of a leading company in the beauty industry based on a purpose-built framework focused on omnichannel capabilities. It finds that, while the company is strong in providing capabilities enabling accessibility of information and creating enjoyment throughout the customer journey, there are significant improvement opportunities in flexibility, speed, and cost savings. It, then, recommends addressing these opportunities through a deeper collaboration with retailers, which has the potential to create value for both partners by integrating their in-store experience, customer interaction, and digital footprint.